Overexpression of DAZL, STRA8, and BOULE Genes and Treatment With BMP4 or Retinoic Acid Modulate the Expression of MSC Overexpressing Germ Cell Genes - Cordero, Paloma; Guerrero-Moncayo, Alejandra; De los Reyes, Monica; Varas-Godoy, Manuel; Cortez, Jahaira; Torres, Cristian G.; Parraguez, Victor H.; Peralta, Oscar A. (Frontiers in Veterinary Science, 2021)
In vitro gamete derivation from stem cells has potential applications in animal reproduction as an alternative method for dissemination of elite animal genetics, production of transgenic animals, and conservation of endangered species. Mesenchymal stem cells (MSCs) may be suitable candidates for in vitro gamete derivation considering their differentiative capacity, and their potential for cell therapy. Due to its relevance in gametogenesis it has been reported that retinoic acid (RA) and bone morphogenetic protein (BMP) 4 are able to up-regulate expression of specific markers associated to early stages of GC differentiation in bovine fetal MSCs (bfMSCs). In the present study we used polycistronic vectors containing combinations of GC genes DAZL, STRA8 and BOULE followed by exposure to BMP4 or RA to induce GC differentiation of bovine fetal adipose tissue-derived MSC (AT-MSCs). Cells samples at Day 14 were analyzed according to the expression of pluripotency genes NANOG and OCT4 and GC genes DAZL, STRA8, BOULE, PIWI, c-KIT and FRAGILIS using Q-PCR. Fetal and adult testis and AT-MSCs samples were also analyzed for expression of DAZL, STRA8 and NANOG using immunofluorescence. Increased gene expression levels in adult testis and cell-specific distribution of DAZL, STRA8 and NANOG in fetal testis suggest that these markers are important components of the regulatory network that control in vivo differentiation of bovine GCs. Overexpression of DAZL and STRA8 in bi-cistronic and DAZL, STRA8 and BOULE in tri-cistronic vectors resulted in upregulation of OCT4, NANOG and PIWIL2 in bovine fetal AT-MSCs. While BMP4 repressed NANOG expression, this treatment increased DAZL and c-KIT and activated FRAGILIS expression in bovine fetal AT-MSCs. Treatment with RA for 14 days increased expression of DAZL and FRAGILIS and maintained mRNA levels of STRA8 in bovine fetal AT-MSCs transfected with bi-cistronic and tri-cistronic vectors. Moreover, RA treatment repressed expression of OCT4 and NANOG in these cells. Thus, overexpression of DAZL, STRA8 and BOULE induced upregulation of pluripotency markers and PIWIL2 in transfected bovine fetal AT-MSCs. BMP4 and RA partial activation of GC gene expression suggest that both factors possess common targets but induce different gene expression effects during GC differentiation in overexpressing bovine fetal AT-MSCs.